PENERAPAN POSISI PRONE PADA BAYI DENGAN MASALAH RESPIRATORY DISTRESS SYNDROME: LITERATURE REVIEW - Marwasariaty; Putri Nur Ainun Sakaria; Ajeng Dwi Retnani (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2024)
Respiratory distress syndrome (RDS) is an acute and serious lung condition affecting the breathing of infants, especially those born prematurely, where the baby is unable to perform normal gas exchange without assistance. One of the non-invasive actions taken to increase SpO2 is the Prone Position. The purpose of writing Literature Review is to analyze the application of Prone Position in infants with Respiratory Distress Syndrome problems. The method used is Literature Review with articles published in the period 2018-2023, from 766 articles found on Google Scholar that meet the inclusion and exclusion criteria there are 3 articles. The results of the study obtained the effectiveness of the application of the Prone Position to increase Oxygen Saturation in Infants with Respiratory Distress Syndrome. The conclusion if this position is done for 2 hours / shift then the Prone Position is effective for increasing Oxygen Saturation. So the more often the Prone is given, the better the O2 exchange in the body.